Comment conjuguer un nouveau gender et de nouveaux genres - Silvia Contarini (Itinéraires)
In order to investigate the articulation between artistic pratice and gendered theorization of such pratice in the context of the futurist avant-garde, the present article analyzes the works of two futurist women, Rosa Rosà and Enif Robert. The hypothesis it develops is that gender issues are present in their work, and that both authors appropriate futurist principles in order to elaborate them in terms of gender, but that their artistic productions reveal even more so than their discourses the limits of their thinking on woman.